Analisis Pengaruh Kualitas Pelayanan Wali Nagari Terhadap Kepuasan Masyarakat dalam Meningkatkan Perekonomian Pada Nagari Ujung Gading Kabupaten Pasaman Barat - Adelia Adelia; Marliyah Marliyah (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
This research was conducted with the aim of knowing how the Effect of the Quality of Service of the Nagari Wali on Community Satisfaction in Improving the Economy of Nagari Ujung Gading. In this study, the incidental sampling technique was used as a sampling technique. the purpose of the incidental sampling technique is that the sample is selected by chance, in other words, everyone the researcher meets by chance can be used as a sample if those encountered are considered appropriate as a source of information or data. The sample in this study was the Ujung Gading community. In this study, the data were analyzed using a simple linear regression test, then the hypothesis was tested by testing the coefficient of determination (R²) and partial test (t). Furthermore, the data was processed using SPSS software. The results obtained in the study show that the quality of service at Wali Nagari Ujung Gading, West Pasaman Regency, partially has a positive and significant impact on community satisfaction in improving the economy.